The Impact of XmnI-HBG2, BCL11A and HBS1L-MYB Single Nucleotide Polymorphisms on Hb F Variation of Hematologically Normal Iranian Individuals. (3rd May 2016) - Keyhani, Elaheh; Jafari Vesiehsari, Mahjoobeh; Talebi Kakroodi, Setareh; Darabi, Elham; Zamani, Fahimeh; Karimlou, Masoud; Kamali, Koorosh; Neishabury, Maryam
Abstract: The impact of Hb F on severity of sickle cell disease and β-thalassemia (β-thal) is well documented. The Xmn I- HBG2, BCL11A and HBS1L-MYB single nucleotide polymorphisms (SNPs) have been introduced as the most important factors causing variation in fetal hemoglobin (Hb F) levels in different population studies. However, the extent of their effect could be population-specific. In this study, multivariate linear regression analysis was used to evaluate the association of Hb F with age, sex, and eight SNPs, including Xmn I- HBG2, four BCL11A, two HBS1L-MYB SNPs and the polymorphic palindromic 5′ hypersensitive 4-locus control region (5′HS4-LCR). One hundred and twenty-two hematologically normal individuals, from a previous study cohort, constituted our study population. In multivariate regression analyses, no association of Hb F was observed with age or sex of the individuals and SNPs in this study. We conducted a univariate regression analysis to further investigate the results, which among all the factors only detected Xmn I- HBG2 and 5′HS4 SNPs as significant modifiers of Hb F. The significance of these two factors disappeared in a bivariate analysis. These results suggest that either Xmn I- HBG2 or 5′HS4-LCR have a stronger contribution in Hb F variations of the Iranian population than BCL11A and HBS1L-MYB SNPs. Furthermore, the effect of low population size and technical limitations on obtained results could not be ruled out.